2004
DOI: 10.1680/geot.54.3.203.36349
|View full text |Cite
|
Sign up to set email alerts
|

An alternative mechanism of pile failure in liquefiable deposits during earthquakes

Abstract: This paper proposes an alternative mechanism of pile failure in liquefiable deposits during earthquakes. This failure mechanism, based on pile buckling, is formulated by back-analysing 14 case histories of pile foundation performance during earthquakes and verified using dynamic centrifuge tests. A new parameter, the slenderness ratio of a pile, is introduced to classify pile performance in liquefiable soils. This parameter fits very well both the reported case histories and the centrifuge test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In contrast to the bending failure mechanism, investigations carried out by Bhattacharya et al [19], Lin et al [20], Kimura and Tokimatsu [21], Shanker et al [22], Bhattacharya et al [23] and Knappett and Madabhushi [24] have demonstrated that when soil liquefies and loses much of its stiffness, end-bearing piles act as unsupported long slender columns and may buckle under the action of the axial load arising from the dead load of the superstructure. A comprehensive critical review of the current theories of pile failures and hypothesis behind the current codes of practice may be found in [25].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the bending failure mechanism, investigations carried out by Bhattacharya et al [19], Lin et al [20], Kimura and Tokimatsu [21], Shanker et al [22], Bhattacharya et al [23] and Knappett and Madabhushi [24] have demonstrated that when soil liquefies and loses much of its stiffness, end-bearing piles act as unsupported long slender columns and may buckle under the action of the axial load arising from the dead load of the superstructure. A comprehensive critical review of the current theories of pile failures and hypothesis behind the current codes of practice may be found in [25].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2. Schematic Diagram for Pile Failure(Bhattacharya, 2003)Bhattacharya et al (2004), investigated the behavior of 14 pile foundation system in liquefiable soils with 1/50 g centrifuge tests. In tests, tank with dimensions of 560 mm x 235 mm x 220 mm and aluminium piles with outer diameter of 9,3 mm and inner diameter of 8,5 mm are used.…”
mentioning
confidence: 99%